Agarose-Based Antibacterial Films from Gracilaria sp.: Isolation, Characterization, and Metal Nanoparticle Incorporation - Ahmad, Ahyar; Zainuddin, Rahmaniah; Saksono, Budi; Anita, Sita Heris; Zulfiana, Deni; Ermawar, Riksfardini A.; Arfah, Rugaiyah; Natsir, Hasnah; Karim, Harningsih; Irmawati; Ramli, Siti R.; Karim, Abdul (Ital Publication, 2025)
The incorporated metal nanoparticles in a polysaccharide-based film exhibit efficient antibacterial activity against harmful germs. However, previous studies have used a commercial polysaccharide for their film production. Therefore, this study aimed to develop a natural polysaccharide-based film extracted from the local algae Gracilaria sp. originating from Sinjai Regency, South Sulawesi, Indonesia. Firstly, the polysaccharide agarose was isolated and its properties compared with those of commercial agarose. A present low-cost isolation process produces agarose with 1.8% (w/w) of yield. Results also showed physicochemical properties similar to those of the commercial agarose. Secondly, the agarose-based antibacterial film was synthesized at 0, 0.5, and 1% glycerol concentrations. The synthesized film was incorporated with silver (Ag) and copper (Cu) nanoparticles (NPs). Morphological, mechanical, and physicochemical properties of the incorporated Ag-agarose and Cu-agarose films were characterized using Field Emission Scanning Electron Microscope (FESEM), Universal Testing Machine (UTM), and Fourier Transform Infrared Spectroscopy (FTIR), respectively. Results showed the film stiffness and tensile strength increased by incorporating either AgNPs or CuNPS. The interaction of AgNPs-agarose most likely involves physical bonds, while the interaction of CuNPs-agarose forms coordination bonds. An antibacterial test showed that the Ag-agarose nanocomposite inhibited the growth of Escherichia coli, Salmonella typhimurium, Staphylococcus aureus, Staphylococcus epidermidis, and Bacillus subtilis. In the meantime, Cu-agarose prevented the growth of Staphylococcus aureus. Overall, antibacterial activity was influenced by the interaction between metal nanoparticles and agarose, the concentration of metal nanoparticles, and the film's solubility. An agarose-based antibacterial film from Gracilaria sp. has the potential for use in various applications, including food packaging, pharmaceuticals, and other industries.